ANALISIS POTENSI AIR TANAH BERDASARKAN PENGUKURAN GEOLISTRIK 2D DI DAERAH KAPUAS, PROVINSI KALIMANTAN TENGAH - Naryanto, Heru Sri; nurhidayat, nurhidayat (Center for Environmental Technology, 2014)
Groundwater is water that occurs naturally in the subsurface, and is contained in the aquifer. Groundwater is the water source of the most widely used by the public for purposes of clean water. To determine the condition of the aquifer configuration one of the methods that can be used is the 2D electrical resistivity. Exploration drilling is one effective way to determine directly the presence of groundwater, but to determine the location of the drilling necessary geophysical approach to describe subsurface conditions prior to drilling. 2D electrical resistivity method is a geophysical method that utilizes dynamic electrical properties of the media path. 2D electrical resistivity measurements have been carried out in Kapuas, Central Kalimantan using Wenner configuration, the distance between the electrodes 10 meters, penetration depth reaches 80 meters, and and measuring some 21 track. Water potential zones were identified based on having resistivity range 15-25 ohm.m, contained in the sandstone layer, which is covered in a layer of impermeable mudstone layers. Location that has a high potential for groundwater recommended drilling done on the track P-07 and P-13, with an estimated depth of the aquifer between 25 meters and 30 meters. The highest groundwater potential lies between the drilling data PH-23 and PH-24, with the resistivity at that point reaches 300 ohm.m.Ã‚Â Keywords : Groundwater, aquifer, sandstone, 2D electrical resistivity, resistivity, Kapuas